An overview: Recycling of solid barley waste generated as a by-product in distillery and brewery. (April 2017) - Nigam, Poonam Singh
Highlights: Recycling of wastes generated in distillery and brewery. Options for reuse of Barley spent grains. Processing in non-microbiological processes. Bioprocessing for products of commercial application. Abstract: This overview has focused on the options available for the utilisation of residual-biomass generated in distillery and brewery for the production of added-value products. Bio-processing approaches have been reviewed and discussed for the economical bioconversion and utilisation of this waste for the production of bioproducts, such as lactic acid, enzymes, xylitol and animal feed. Though this overview provides several options for the bioprocessing of this residual material, a more suitable one could be chosen according to the processing-facilities available and the amount of residue available in local area. The feasibility of any chosen process should be evaluated on the basis of cost of material available, its local utilisation for animal feed, and the overall economical advantages that could be gained by changing its current traditional landfill use to produce higher added value products.